PRODUKSI TANAMAN STROBERI PADA BERBAGAI JENIS PUPUK ORGANIK CAIR DENGAN SISTEM HIDROPONIK IRIGASI TETES - NURLAILAH MAPPANGANRO; BAHARUDDIN BAHARUDDIN (GANEC SWARA, 2021)
Strawberries are one type of fruit that has high economic value.  The research aimed at investigating the effect of the liquid organic fertilizer from the cattle dung, the cow urine on the production of the strawberry plant, and the effect of the liquid organic fertilizer from the cattle dung and cow urine on the production of the strawberry plant. The research was designed by using complete randomized design with three replications with 36 treatments of the types and concentrations of the liquid organic fertilizer and cow urine.  The result of the research indicates that the cow liquid organic fertilizer gives the best results on production of the strawberry, whereas the rabbit liquid organic fertilizer  gives the best results on the age of fruiting, number of fruit, fruit length, fruit diameter, fruit weight and the production of every strawberry plant.  The addition of the cow urine (50 mL/L) gives the best result on production of the strawberry plant.  The rabbit liquid organic fertilizer (6 mL/L) and the cow urine (50 mL/L) give the best results on the age of fruiting, number of fruit, fruit length, fruit diameter, fruit weight, and the production of every strawberry plant.